The effect of T-lysine cream on the wound healing process - Asmaa Awni Haydar (Zanco Journal of Medical Sciences, 2023)
Background and objective: Wound healing is a dynamic process that can be compromised in patients with chronic and metabolic conditions or unhealthy lifestyles. Objectives of study is to demonstrate a hyaluronate-containing supramolecular structure which enhances repalysYAL®cream effectiveness, sodium chloride with thymine (T-LysYal®); 1) notable progress in the healing of wounds. 2) the production of minuscule collagen strands 3) a shorter recovery period. Methods: Case study, the test group received standard treatment followed by lysine cream to indicate the size and depth ulcer from the 1st week to the 3rd week. Our patients were a 1-year child and 29 years old male who presented with a second degree of total body surface area (TBSA) burn and skin grafts at the burn center of Rozhawa Hospital/ Hawler/Iraq. The observations were approved by the Ethics committee college of pharmacy in compliance with the ethical standard. Initially assessed as superficial partial-thickness in-depth, the wounds were treated conservatively with dressings and repalysYAL® cream 2-3 times per day; however, represents the healing process in short-term individual therapy. Results: In case 1; The patient had been exposed to flash deep burn to the right palm (thermal injury) mainly of superficial partial thickness; any necrotic tissue present needs to be removed to take full advantage of the product’s potential. When (repalysYAL®) cream is used, there will be a physiological increase in the exudate, which will have to be managed to avoid maceration. While in case 2;The patient presented surgical wound dehiscence in the inner compartment of the left foot with leakage of purulent material and signs of necrotizing fasciitis. with using (repalysYAL®) cream, the wound reduces scar formation due to 90% and increase fibroblast by 30% when a blood vessel is formed to which blood is supplied, the cells are cultivated and divided to form new tissue and an organ. Conclusion: Signaling pathways that induce cellular and tissue responses after injury, ...